Menakar Hermeneutika Alkitab Dalam Analisis Sastra - Jemima Shalom; Netti Rismawati (SERVIRE: Jurnal Pengabdian Kepada Masyarakat, 2021)
The content of the Bible is so diverse among them literature in understanding the purpose and purpose in literature the author studied with the study of literature in order to understand how to interpret with the genre of literature. From the researchers get that this analysis reveals the Word of God is not an inspired language but writing, language only as a medium of communication from God to man, and poured into a text or writing. Isi Alkitab begitu beragam diantaranya sastra dalam memahami maksud dan tujuan dalam sastra penulis mengkaji dengan kajian studi pustaka agar dapat memahami cara menafsir dengen genre sastra. Dari peneliti mendapatkan bahwa analisis ini mengungkapkan Firman Tuhan bukan bahasa yang diilhamkan tetapi tulisan, bahasa hanya sebagai media komunikasi dari Tuhan untuk manusia, dan dituangkan menjadi suatu teks atau tulisan.